Morphological Outer Retina Findings in Multiple Sclerosis Patients With or Without Optic Neuritis - Ziccardi, Lucia; Barbano, Lucilla; Boffa, Laura; Albanese, Maria; Grzybowski, Andrzej; Centonze, Diego; Parisi, Vincenzo (Frontiers in Neurology, 2020)
Purpose: To investigate on the morphology of the macular inner (IR) and outer (OR) layers in multiple sclerosis (MS) patients with and without history of optic neuritis (ON), followed by good or poor recovery of best corrected visual acuity (BCVA). Methods: Thirty-five normal control subjects and 93 relapsing remitting MS patients were enrolled. Of this, 40 MS patients without ON (MS-noON, 40 eyes), 27 with history of ON and good BCVA recovery (MS-ON-G, 27 eyes), and 26 with history of ON and poor BCVA recovery (MS-ON-P, 26 eyes) were studied. Controls and MS patients underwent an extensive ophthalmological examination including spectral-domain optical coherence tomography evaluating in 3 localized macular areas (0–1 mm, Area 1; 1–3 mm, Area 2; 3- 6 mm, Area 3), volumes (MV), and thicknesses (MT) of the whole retina (WR), further segmented in IR and OR. The differences of MV and MT between the groups were tested by ANOVA. In the MS-ON-P group, the correlations between MV and MT and BCVA were evaluated by Pearson's test. Results: When compared to controls, the MS-noON group showed not significantly (p > 0.01) different MVs, whereas MTs were significantly (p < 0.01) reduced in the evaluation of WR and IR. In the MS-ON-G group, a significant (p < 0.01) reduction of WR and IR MVs and MTs was found in Areas 2 and 3; OR MVs and MTs were similar (p > 0.01) to controls. In the MS-ON-P group a significant (p < 0.01) reduction of WR, IR, and OR MVs and MTs was detected in all areas; the BCVA reduction was significantly (p < 0.01) correlated with WR and IR MVs and MTs. Conclusions: In MS without history of ON or when ON is followed by a good BCVA recovery, the neurodegenerative process is limited to IR macular layers; in the presence of ON, with a poor BCVA recovery, a morphological impairment of both IR and OR macular layers occurs.